Peran Manajemen SDM Dalam Meningkatkan Kinerja Dan Retensi Tenaga Kesehatan: Kajian Literatur - Inayyah Nur Fitry Sirajuddin (STIKES Columbia Asia Medan, 2025)
This study aims to analyze the role of human resource management (HRM) in improving performance and retention among healthcare professionals in health service facilities. Using a systematic literature review approach based on the PRISMA method, this study reviewed 25 international and national journal articles published between 2015 and 2025. The findings indicate that strategic HRM practices—such as competency-based recruitment, continuous professional development, fair compensation, and transformational leadership—positively influence both performance and retention of healthcare workers. Additionally, factors like organizational culture, work-life balance, and psychological well-being play a mediating role in enhancing job satisfaction and organizational commitment. The results highlight that HRM practices are not merely administrative functions but strategic elements that determine healthcare organizations’ sustainability and competitiveness. The study contributes to the development of theoretical frameworks in strategic HRM and provides practical recommendations for healthcare managers to design more adaptive, fair, and human-centered HR policies.